School heads and mentors in cahoots? Challenges to teaching practice in Zimbabwean teacher education programmes - Makura, Alfred Henry; Zireva, Davison (Journal of Sexual Aggression, 2013)
Mentors and school heads play cardinal roles in teacher education programmes in most countries, including Zimbabwe. The side-effects of such symbiosis have not yet been investigated fully. This article used a qualitative methodological approach to investigate the perceptions of some Zimbabwean student teachers regarding their teaching practice experiences. A sample of 10 exteaching practice students from a teacher education college was selected and interviewed during data collection using a semi-structured interview schedule. The participants reported a high prevalence of sexual harassment/aggression of the students by the host schools’ heads and mentors, irrespective of student gender. The form of aggression included seeking sexual favours and intimidation. Most perpetrators used metaphors and satirical or sarcastic language to convey their intentions. The female student teachers reported higher incidences than did the male students. Constant workshopping is imperative to remind mentors and school heads of their professional and social obligations regarding teacher education.
Published Article
Keywords: Mentors; school heads; student teac; sexual harassment; teaching practice; Zimbabwe